Proceedings of International Symposium and Exhibition on Formation Damage Control 2006
DOI: 10.2523/98261-ms
|View full text |Cite
|
Sign up to set email alerts
|

From Laboratory Research to Successful Practice: A Case Study of Carbonate Formation Emulsified Acid Treatments

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractAfter laboratory research the pilot treatment has been done. After obtaining positive results from this treatment, BMB oil field operator begun to use emulsified acid for small scale acidizing treatment on production wells. Six acidizing treatments have been performed using emulsified acid. Oil and gas production increase was achieved after each treatment. Significant oil and gas production increase and decrease of near wellbore pressure drop was noticed duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…Using a constant emulsifier concentration in a rotating disk experiment, Al-Mutairi et al studied the effect of temperature on the diffusivity of emulsified HCl on the surface of a calcite rock. The results indicated that any increment in the system temperature led to an increase in the acid diffusion coefficient, and even though this was unlike what was reported in refs and the result did not obey Arrhenius’s law.…”
Section: Factors Impacting Diffusion Coefficient Magnitudecontrasting
confidence: 75%
“…Using a constant emulsifier concentration in a rotating disk experiment, Al-Mutairi et al studied the effect of temperature on the diffusivity of emulsified HCl on the surface of a calcite rock. The results indicated that any increment in the system temperature led to an increase in the acid diffusion coefficient, and even though this was unlike what was reported in refs and the result did not obey Arrhenius’s law.…”
Section: Factors Impacting Diffusion Coefficient Magnitudecontrasting
confidence: 75%
“…Several studies (De Rozieres et al 1994;Navarrete et al 1998;Conway et al 1999;Kasza et al 2006;Al-Mutairi et al 2009) examined the reaction rate of emulsified acid with carbonates. Navarrete et al (1998) indicated that the reaction rate of 28 wt% HCl emulsified acid with limestone was 8.5 times slower than that of regular acid that contained 28 wt% HCl with limestone.…”
Section: Emulsified Acid Systemmentioning
confidence: 99%